2015
DOI: 10.1016/j.cbpb.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of folate intake on DNA and single-carbon pathway metabolism in the fruit fly Drosophila melanogaster compared to mammals

Abstract: Mechanisms of vitamin function in non-mammals are poorly understood, despite being essential for development. Folate and cobalamin are B-vitamin cofactors with overlapping roles in transferring various single-carbon units. In mammals, one or both is needed for nucleotide synthesis, DNA methylation, amino acid conversions and other reactions. However, there has been little investigation of the response to folate or cobalamin in insects. Here, we manipulated folate intake and potentially cobalamin levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The influences of different bacterial strains on life history traits in fruit flies reared on our nutrient-rich diet led to correlated phenotypes, where bacteria that conferred shorter starvation resistance and life span also conferred higher early reproduction and development rates and lower fat storage (41). Since bacterial methionine metabolism influences both life span and starvation resistance, though this work shows such effects are not necessarily through the same genes, and because of established work showing that levels of methionine cycle metabolites in the diet influence fly reproduction and development rate (8,12,45), bacterial methionine metabolism may be a key trait underlying microbial influences on D. melanogaster life history traits. A counterargument is that tradeoffs between reproduction and fecundity can be decoupled by rearing flies on different diets and that these relationships may only be apparent under particular dietary or other scenarios (8,12).…”
Section: Discussionmentioning
confidence: 89%
“…The influences of different bacterial strains on life history traits in fruit flies reared on our nutrient-rich diet led to correlated phenotypes, where bacteria that conferred shorter starvation resistance and life span also conferred higher early reproduction and development rates and lower fat storage (41). Since bacterial methionine metabolism influences both life span and starvation resistance, though this work shows such effects are not necessarily through the same genes, and because of established work showing that levels of methionine cycle metabolites in the diet influence fly reproduction and development rate (8,12,45), bacterial methionine metabolism may be a key trait underlying microbial influences on D. melanogaster life history traits. A counterargument is that tradeoffs between reproduction and fecundity can be decoupled by rearing flies on different diets and that these relationships may only be apparent under particular dietary or other scenarios (8,12).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a recent study by Blatch et al . in Drosophila showed that several metabolites, associated with OCM (cystathionine, methylgycine, and methylmalonic acid), were disrupted in larvae consuming MTX 51 ; providing evidence that MTX may affect OCM in invertebrates.…”
Section: Discussionmentioning
confidence: 92%
“…It has recently been reasoned that invertebrates (specifically insects) are suitable organisms for studying human diseases with an epigenetic component, due to conservation of underlying molecular mechanisms 56 . Additionally, despite being vital for development in non-mammalian species the mechanisms of vitamin function are poorly understood in invertebrates 51 . The observations outlined in our investigation, showing a link between vitamin B 12 availability or MTX exposure and levels of DNA methylation, provide novel information on nutritional mechanisms in a non-mammalian species.…”
Section: Discussionmentioning
confidence: 99%
“…Folate is a cofactor that transfers single-carbon units (e.g., CH 3 and CHO) in numerous reactions. One-carbon metabolism includes nucleotide synthesis (purine ring and thymidine from uridine; Supplementary Fig 4 and 1) (Blatch et al, 2015). Thus, insufficient folate would result in the inadequate production of thymidine and possible misincorporations of uracil in DNA (Blount et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, insufficient folate would result in the inadequate production of thymidine and possible misincorporations of uracil in DNA (Blount et al, 1997). Insects also appear to require folate for nucleotide synthesis (Blatch et al, 2015). Folate deficiencies decrease SAM levels and DNA methylation levels, which then disrupt gene regulation in mice (Friso and Choi, 2002).…”
Section: Discussionmentioning
confidence: 99%